Birthing the computer : from drums to cores - Kaisler, Stephen H. (Stephen Hendrick) (Cambridge Scholars Publishing, 2017)
Birthing the Computer: From Drums to Cores examines the evolution of computer systems architecture based on two evolutionary developments: memory technology - magnetic drums to magnetic cores - and CPU technology - transistors. This evolution, exemplified by a number of academic and commercial computing machines, yielded significant performance improvements and more storage leading to more effective utilization. These features would drive the development of programming languages and system software that would enhance the usability of the machines to solve more complex problems in both business.